Livedoid Vasculopathy Presenting in a Patient With Sickle Cell Disease. (September 2018) - Reagin, Heather; Marks, Etan; Weis, Stephen; Susa, Joseph
Abstract : Abstract: We report a case in which a 43-year-old African American male with medical history of sickle cell disease (SCD) presented with a nonhealing ulcer. Biopsy revealed features of livedoid vasculopathy. Previously, livedoid vasculopathy had only been described in a patient with sickle cell trait, but never in a patient with SCD. Livedoid vasculopathy most commonly affects the distal lower extremities and is characterized by irregular, punched-out, painful ulcers that heal with stellate white scars of atrophie blanche. Histologically, it reveals segmental hyalinizing vessels, focal thrombosis, and endothelial proliferation. The etiology is currently unclear, but it has been shown to be related to procoagulant states and a diagnosis of livedoid vasculopathy should prompt a thorough hypercoagulable workup, including testing for SCD in high-risk patients.